Two-Place Exceed Comparatives in Luganda - Bochnak, Ryan (My University, 2018)
Research on comparative constructions recognizes the need for both a 3-place (“phrasal”) comparative operator, alongside a 2-place (“clausal”) operator (e.g., Heim 1985; Bhatt & Takahashi 2011). Recent cross-linguistic work on comparatives has argued that exceed comparative constructions are phrasal comparatives, making use of a 3-place operator (e.g., Beck et al. 2009; Howell 2013 for Yorùbá). While certain exceed constructions in Luganda can indeed be analyzed in this way, I argue here for the idea that others involve a 2-place operator that compares two degrees directly. I treat nominalized adjectives as measure functions in the sense of Bartsch & Vennemann 1972 and Kennedy 1997: they map an individual to its maximal degree on a scale. This allows us to model possessed adjective nominalizations similar to Barker’s (1995) analysis of relational nouns, although whereas for Barker a possessive DP denotes a predicate of individuals, in this case the resulting DP denotes a degree.
Keywords: Luganda; comparatives; Two-place